Electrical discharge machining by rapid tools prepared by micro stereo-lithography process with copper metallization - Anshuman Kumar Sahu; Siba Sankar Mahapatra; André Martin; Andreas Schubert; Marco Leite; Paulo Peças (Scientific Reports)
Abstract Rapid tooling (RT) has evolved into an emerging area in the field of manufacturing for fabricating tools potentially reducing machining time and cost allowing higher levels of geometric freedom. In this work, the application of RT technique in electrical discharge machining (EDM) has been explored. RT tools fabricated by micro stereo-lithography (micro-SLA) are coated with thick copper coatings by electroless metallization and electroplating to be used during EDM to machine 304 L stainless steel work piece material. The performance of the RT tools is compared with massive copper tool results considering output performance measures like material removal rate, tool wear rate, surface roughness, and surface crack density. The machined work piece surfaces and tool surfaces are analyzed using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). The proposed RT tools have shown a higher material removal rate than the conventionally used massive copper tool. In addition, micro-cracks formed on the machined surfaces using RT tools are comparatively less. Nevertheless, the RT tools have higher tool wear rate and higher surface roughness on the machined surfaces as compared to the massive copper tool.